2020
DOI: 10.1177/2156759x19899179
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Educational Resilience and Opportunities in Urban Schools Through Equity-Focused School–Family–Community Partnerships

Abstract: Over the past two decades, research on urban schools has focused predominantly on achievement gaps. However, achievement gaps exist because of gaps in opportunities for urban, low-income, and racially/ethnically diverse students. Partnerships among schools, families, and communities can provide the enrichment opportunities, support, resources, and programs that students need to be educationally resilient despite adversity. School counselors are in a unique position to promote resilience through equity-focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(125 citation statements)
references
References 61 publications
4
112
0
9
Order By: Relevance
“…This is especially true in urban areas with high concentrations of poverty or unemployment. For instance, low-income urban students are more likely than their suburban or rural peers to be exposed to environments that do not foster educational and economic success, such as poverty, unemployment disparities; gang violence; under-resourced neighborhoods; homelessness; frequent mobility; inadequate educational experiences, and limited resources and services (Bryan, 2005;Chau, Thampi, & Wight, 2010). These urban students are also more frequently educated in schools with fewer certified teachers; less-rigorous curriculum, less access to technology (Barton & Coley, 2009); less parental involvement in education, both at the school and in the home; fewer social support networks (Brady-Smith, Fauth, & Brooks-Gunn, 2003;Evans, 2004;Moore, Redd, Burkhauser, Mbwana, & Collins, 2009); lower per pupil expenditures; lower teacher expectations concerning their academic performance (Barton, 2003;Bennett et al, 2004;Carey, 2002); disparities in school-based services and resources; and less access to books, computers, and other devices that stimulate or improve learning (Evans) in comparison to their suburban and rural peers (Barton; Bennett et al; Carey).…”
Section: List Of Tablesmentioning
confidence: 99%
“…This is especially true in urban areas with high concentrations of poverty or unemployment. For instance, low-income urban students are more likely than their suburban or rural peers to be exposed to environments that do not foster educational and economic success, such as poverty, unemployment disparities; gang violence; under-resourced neighborhoods; homelessness; frequent mobility; inadequate educational experiences, and limited resources and services (Bryan, 2005;Chau, Thampi, & Wight, 2010). These urban students are also more frequently educated in schools with fewer certified teachers; less-rigorous curriculum, less access to technology (Barton & Coley, 2009); less parental involvement in education, both at the school and in the home; fewer social support networks (Brady-Smith, Fauth, & Brooks-Gunn, 2003;Evans, 2004;Moore, Redd, Burkhauser, Mbwana, & Collins, 2009); lower per pupil expenditures; lower teacher expectations concerning their academic performance (Barton, 2003;Bennett et al, 2004;Carey, 2002); disparities in school-based services and resources; and less access to books, computers, and other devices that stimulate or improve learning (Evans) in comparison to their suburban and rural peers (Barton; Bennett et al; Carey).…”
Section: List Of Tablesmentioning
confidence: 99%
“…There is evidence that school counselors believe that SFC partnerships are important (e.g., Bryan, 2005;Bryan & Holcomb-McCoy, 2004Dimmitt, 2003;Simcox, Nuijens, & Lee, 2006). Holcomb-McCoy (2004, 2007) examined school counselors' perceptions of partnerships and their studies suggest that in spite of a range of obstacles, such as administrative tasks, too many roles and functions, time limitations for developing and implementing partnership programs, school counselors believed in the efficacy of collaborative partnership programs.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Partnerships among school stakeholders are especially relevant for school counselors who find themselves in the position to implement wide-ranging solutions to various issues (e.g., homelessness, poverty, academic failure, school alienation) that many students encounter (Bryan, 2005). School counselors reported that partnerships with multiple stakeholders often result in innovative solutions to complex student problems (Bryan & Henry, 2008).…”
Section: Membersmentioning
confidence: 99%
See 2 more Smart Citations